Manajemen Usahatani Salak Bali Organik di SubakAbian Kebon Desa Nongan Kecamatan Rendang Kabupaten Karangasem - SUDIARMINI, NI WAYAN; ASTITI, NI WAYAN SRI; PARINING, NYOMAN (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.7, No.4, Oktober 2018DO - 10.24843/JAA.2018.v07.i04.p12, 2018)
Management of Organic Salak Farming System in Nongan Village, Rendang Sub-district, Karangasem Regency Farm management covers the management functions that include: planning, organizing, implementation and monitoring of the production process. This process is related to the plant maintenance to the marketing. It is expected that through the implementation of farm management function, farmers in Subak Abian Kebon will be able to carry out farming activities well and to increase the farmers' income for the common welfare. The purpose of this study is to determine the implementation of management functions in the salak (snake fruit) farming activities in the Subak Abian Kebon. The location of the research was in Subak Abian Kebon of the Nongan Village, Rendang Sub-District, Karangasem Regency, taken by purposive sampling.The total population is 76 people and the number of respondents is 44 people taken based on the Slovin formula. Data analysis used is qualitative descriptive analysis. The results showed that management functions in farming activities in the Subak of AbianKebon can be classified as very good with the score achievement of 3.9. This is proven by the good farming planning with the achievement score of 4.0, good farming organization with achievement score of 4.0, the implementation of farming is very good with achievement score of 4.3 and supervision that can be categorized as moderate, with the achievement score of 3.4. It can be suggested that the subak members should be able to improve supervision on the production quality and the government is expected to pay attention to the market access for subak in order to increase the demand for the fruits considering that Nongan Village is a tourist route to Besakih Temple.